Effect of hip dysplasia on the development of the femoral head growth plate - Ren, Ningtao; Zhang, Zhendong; Li, Yong; Zheng, Ping; Cheng, Hui; Luo, Dianzhong; Zhang, Jianli; Zhang, Hong (Frontiers in Pediatrics, 2023)
The purpose of this study was to observe whether developmental dysplasia of the hip (DDH) affects the development of the femoral head growth plate and to analyze the risk factors.We selected female patients aged between 11 and 20 years with unilateral DDH and unclosed femoral head growth plate(s). The selected patients underwent anteroposterior radiography of the hip joint to compare the degree of development of the femoral head growth plate on both sides and to identify risk factors that affect the development of the growth plate in the femoral head.We included 48 female patients with unilateral DDH, with an average age of 14 years (range: 11.1-18.5 years) and an average BMI of 20.4 kg/m² (range: 15.5 kg/m²-27.9 kg/m²). Among them, 23 patients had earlier development of the femoral head growth plate on the affected side than on the healthy side, while the degree of development of the femoral head growth plate in 25 patients was the same as that on the contralateral side. When the Tönnis angle was greater than 29.5 degrees and/or the Reimers migration index was greater than 48.5%, there was a statistically significant difference in the acceleration of femoral head growth plate development.An abnormal relative position of the acetabulum-femoral head caused by DDH can accelerate closure of the femoral head growth plate in immature female patients. The risk factors are a Tönnis angle greater than 29.5 degrees and/or Reimers migration index greater than 48.5%.